Relevance of School Facilities and Infrastructure towards Implementing Education Policies - Ibrahim, Yaro (Journal of Social Transformation and Regional Development, 2023)
The purpose of this research is to investigate the relevance of school facilities and infrastructure to sustainable education policy implementation. This has become necessary due to the high global demand for a conducive learning atmosphere for effective knowledge dissemination. Indeed, this could be achieved in a learning environment with adequate school facilities and infrastructure. Using a qualitative research approach with 15 research participants purposely selected among the Sokoto state education stakeholders and analyzed using Nvivo 10 software, it was discovered that the availability of facilities and infrastructure leads to the development of a school system as it facilitates effective teaching and learning and the effective implementation of education policies. The findings also showed that most public schools, especially in Sokoto State, do not have adequate school facilities and infrastructure; hence, they produce substandard graduates. It is therefore recommended that the government intensify efforts to make the required facilities and infrastructure available in schools and judiciously utilize them. The government should also join hands with education stakeholders to collaboratively provide these vital educational ingredients in schools. This is believed to ensure effective teaching and learning, sustainable implementation of the school’s policies, and further guarantee academic excellence for the benefit of present and future generations.